The Application of Psychoanalytic Psychotherapy in Reducing Suicidal Ideation through Ego Functioning Enhancement: A Single-Subject Experiment - Muhammad Fakhrun Siraj; Mulya Virgonita I. Winta; MM. Shinta Pratiwi (Psikostudia : Jurnal Psikologi, 2025)
Suicide is a complex mental health issue often associated with ego dysfunction, including affect regulation, impulse control, and defense mechanisms. This study aims to evaluate the application of psychoanalytic psychotherapy in enhancing ego function and reducing suicidal ideation in a final-year university student. The research employs a single-subject experimental design, measuring ego function before and after the intervention using the Ego Functioning Assessment (EFA). The subject underwent 10 sessions of psychoanalytic psychotherapy, focusing on intrapsychic conflict exploration, transference, and defense mechanisms. The results indicate a significant improvement in all aspects of ego function, particularly in impulse regulation, defense mechanisms, and cognitive processes, contributing to a reduction in the intensity of suicidal ideation. EFA scores showed substantial increases, and the subject transitioned from a neurotic personality organization to a normal personality organization. These findings suggest that psychoanalytic psychotherapy effectively strengthens ego function, which plays a crucial role in mitigating suicide risk. Future research is recommended to include a larger sample and longitudinal evaluation to validate these findings.Bunuh diri merupakan masalah kesehatan mental yang kompleks dan sering dikaitkan dengan gangguan fungsi ego seperti regulasi emosi, kontrol impuls, dan mekanisme pertahanan diri. Penelitian ini bertujuan untuk mengevaluasi penerapan psikoterapi psikoanalisis dalam meningkatkan fungsi ego dan menurunkan ide bunuh diri pada seorang pasien berstatus mahasiswa semester akhir. Penelitian menggunakan eksperimen subjek tunggal dengan pengukuran fungsi ego dilakukan sebelum dan setelah intervensi menggunakan Ego Functioning Assessment (EFA). Subjek menjalani 10 sesi psikoterapi psikoanalisis yang berfokus pada eksplorasi konflik intrapsikis, transferensi, dan mekanisme pertahanan. Hasil penelitian menunjukkan adanya peningkatan dalam semua aspek fungsi ego, terutama dalam regulasi dan kontrol dorongan, mekanisme pertahanan, dan proses pemikiran yang berkontribusi pada penurunan intensitas ide bunuh diri. Skor EFA meningkat secara signifikan dan subjek mengalami transisi dari organisasi kepribadian neurosis ke normal. Temuan ini mengindikasikan bahwa psikoterapi psikoanalisis efektif dalam memperkuat fungsi ego yang berperan dalam mereduksi risiko bunuh diri. Penelitian ini merekomendasikan studi lebih lanjut dengan sampel yang lebih besar dan evaluasi jangka panjang untuk mengonfirmasi temuan ini.